PENGGUNAAN LKS HOTS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA KELAS XI SMA NEGERI 8 PEKANBARU - Gibran '; Yennita '; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the use of HOTS Student Worksheet to improve the thinking ability of high grade students of class XI SMA Negeri 8 Pekanbaru which refers to four indicators, namely Analysis, Evaluation, Inferens and Comparison. The type of research used is quasi experimental research. Subjects of this study were 68 people, namely 34 people in the control class and 34 people in the experimental class. The instrument used in this study is a High Level Thinking Ability Test that amounts to 12 items of objective. Data collection is done by giving test to the research subject. Data is processed descriptively by percentage technique and is explained per HOTS indicator. Based on the result of data analysis indicate that students' high thinking ability in indicator of analysis get percentage 89,22%, Evaluation indicator with percentage 63,73%, indicator of Inferens with percentage 91,18% and indicator Comparison with percentage 53,41%. Thus the use of HOTS student worksheet can improve students' high thinking ability.Keywords: HOTS Student Worksheet, High-Order Thinking Skills